A fulleropyrrolidine with two oligophenylenevinylene substituents: synthesis, electrochemistry and photophysical properties. (2001) - Armaroli, Nicola; Barigelletti, Francesco; Ceroni, Paola; Eckert, Jean-François; Nierengarten, Jean-François
Abstract : A fullerene derivative in which two oligophenylenevinylene (OPV) groupsare attached toC 60 through a pyrrolidine ring has been prepared and photophysical studies inCH 2 CL 2 solution show that photoinduced energy transfer from the OPV moieties toC 60 occurs, and not electron transfer. On passing to a more polar solvent such as benzonitrile, again no evidence of electron transfer is found.